2018
DOI: 10.1016/j.jnucmat.2018.04.044
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation and phase separation of Cl in alkaline earth aluminosilicate glasses

Abstract: Pyrochemical reprocessing of spent nuclear fuels may lead to the generation of chloride containing wastes. 36 Cl wastes may also arise from the treatment of irradiated graphite. Such wastes will have limited solubility in the borosilicates currently used for waste vitrification. Despite requiring higher processing temperatures aluminosilicate glasses show promise for this application. In a series of alkaline earth aluminosilicate glasses we demonstrate that chloride solubility is related to the alkaline earth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…However, since the intensity of Raman peaks is influenced by both concentration and structural ordering, disordered structures such as alkali aluminosilicate geopolymer gels would be expected to show weak Raman bands. 51 In the outer ring of the ion-exchangers, peaks at around 274 cm −1 (280 cm −1 for K-GP), 378 cm −1 , 442 cm −1 , 650 cm −1 , and 895 cm −1 start to appear, the intensities of which increase when moving towards the inner region of the ion-exchanger particles. The locations of these peaks corresponded to those observed for the as-received sodium titanate ion-exchangers (Fig.…”
Section: Dalton Transactions Papermentioning
confidence: 97%
“…However, since the intensity of Raman peaks is influenced by both concentration and structural ordering, disordered structures such as alkali aluminosilicate geopolymer gels would be expected to show weak Raman bands. 51 In the outer ring of the ion-exchangers, peaks at around 274 cm −1 (280 cm −1 for K-GP), 378 cm −1 , 442 cm −1 , 650 cm −1 , and 895 cm −1 start to appear, the intensities of which increase when moving towards the inner region of the ion-exchanger particles. The locations of these peaks corresponded to those observed for the as-received sodium titanate ion-exchangers (Fig.…”
Section: Dalton Transactions Papermentioning
confidence: 97%
“…In addition, CrO 4 2− and Cl − anions can also exist as isolated anions in the glass matrix, similar to the SO 4 2− anions. 46,[52][53][54] The saturated anion concentrations in mol% plotted in Figure 5 demonstrate the competitive behavior of S-Cr and S-Cl anionic species. For glass samples prepared in air, sulfur was assumed to be S(VI) in the form of SO 4 2− .…”
Section: Solubility Of Anions In Glass Matrixmentioning
confidence: 91%
“…A great deal of effort has been spent these last decades to develop specific glass formulations to increase chlorine retention in glasses, especially in the alkaline-earth silicate glass systems (Siwadamrongpong et al 2004, Schofield et al 2009, Tan 2015, Chen et al 2017, Tan and Hand 2018, Zhao et al 2019. Paradoxically, chlorine behavior in glasses is better known than other halogen behavior such as iodine, even though 129 I is of more concern than 36 Cl for geological disposal of nuclear wastes (Meplan and Nuttin 2015, Riley et al 2016, Jolivet et al 2020, Morizet et al 2021a.…”
Section: Introductionmentioning
confidence: 99%
“…Cl solubility in borosilicate glasses is not extensively investigated, as the actual industrial processes are inefficient for Cl retention in glasses at atmospheric pressure (Hrma 2010). The most interesting work yet regarding chlorine behavior in borosilicate glasses is the work by Tan (2015) and Tan and Hand (2018); the latter being limited to the aluminosilicate glass compositions. More recently, Zhao et al (2019) focused mostly on the role of alkaline-earth cations for chlorine incorporation in glasses and concluded that i) Cl solubility in borosilicate glasses increased with the size of the alkaline-earth element, the highest Cl content (2.54 at.%) reached for a Ba-bearing borosilicate glass, ii) the same applied to aluminosilicate glasses, iii) glass composition seemed more important than melting temperature to incorporate Cl in glasses, iv) Cl decreased glass transition temperature in a comparable way to other halogens such as iodine (Jolivet et al 2021) or fluorine (Zimova and Webb 2007), v) Cl affected the polymerization of the glass network, as for iodine (Jolivet et al 2020), and vi) above chlorine saturation, phase separation occurred, but Cl was not necessarily present in the newly formed phase, neither was it retained in the glass.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation